Analysis of parallel operation characteristics of chillers under partial load conditions. (February 2019) - Yulan-Zheng; Liu, Xuefeng; Lu, Zhitao; Fang, Guanyu; Chen, Wenjing; Deng, Shiming
Abstract: The rational allocation of chiller group plays an important role in the efficient operation of generating units. In this paper, the running characteristics of chiller group under full load are studied. Through the construction of the operation model of the chiller group, the relationship between the start and stop collocation and the operation characteristics of the unit group was explored, and the influence of the unit capacity configuration and the number of table number configuration on the running energy consumption characteristics was studied. The results showed that: the greater the difference of host capacity in the group, the lower the energy consumption under full load. In this example, the difference of energy consumption can reach 8%. At the same time, through the increase in the number of generating units, the difference in host capacity within the group had less impact on energy consumption at full load. For a unit group with the same host capacity, the more the number of units was configured, the lower the operating energy consumption. It provided theoretical support for the selection, collocation and operation management of chillers in practical projects.